The digital era. customs and practices - Chamoux, Jean-Pierre (Information systems, web and pervasive computing series., 2022)
For 200 years, industry mastered iron, fire, strength and energy. Today, electronics shape our everyday objects, integrating chips everywhere: computers, phones, keys, games, household appliances, etc. Data, software and calculation frame the conduct of men and the administration of things. Everything is translated into data: the figure is king. This third and last volume of the series examines the creative destruction induced by digital, modifying manners and customs, law, society and politics.